THE DRAWING METHODOLOGY OF STUDYING THE READER’S ATTITUDE TO MEDIA TEXTS: THE OUTLINES AND PROSPECTS FOR IMPROVEMENT - Hurlieva Tetіana (PSYCHOLOGICAL JOURNAL, 2020)
The article focuses on the necessity of the reader to navigate in modern mass media and be willing and able to resist the aggressive manipulative influence by the means of a text, which is based on the analysis of scientific sources and personal research. Nowadays it is relevant to create methodologies that enable the study of the peculiarities of the perception of different kinds of texts in order to help an individual to obtain benefits from the consumed information as well as get or regain emotional balance. The article presents the results of the approbation of the authorial methodology of studying the modern Ukrainian reader’s attitude to media texts, precisely to dialogue-based and manipulative ones. The obtained data of the empirical study prove its relevance as it provides the psychologist with information about the peculiarities of the perception of media texts and attitude to them. Furthermore, it offers guidelines on how to help a citizen to resist the manipulative media-influence and enable them to feel emotionally safe and secure. The knowledge of the peculiarities of the reader’s perception of the text delivers the tools to activate the person’s subjective activity and the urge to take personal responsibility for the consumption of information from Internet sources and printed mass media. The article provides the aspects of the analysis of pictures and the generalisations of the results of the interpretation of the drawings of manipulative and dialogue-based texts by the surveyed. The attitude to media texts is considered from cognitive, emotional and behavioural perspectives. The findings show that the surveyed citizens-readers generally “perceive” and “recognize” both dialogue-based texts and manipulative ones and react to them anyway. Nevertheless, the surveyed sometimes admit to being unable or struggling to identify a fine, almost imperceptible manipulation and thus require professional help. The reader needs to be aided in identifying the influence of a manipulative text on their emotional state and behaviour as well as assisted in resistance to detrimental changes. The article presents the prospect for enhancement and improvement of the projective technique “Dialogue-based and manipulative mass media text: my attitude”. Even though we forecast the further approbation and validation of the drawing test, the question of the reliability of the suggested projective drawing technique remains to be unanswered. We plan to involve expert psychologists to identify important features in the drawings, which are related to the reader’s attitude to texts of different orientations.